Probing liver function test patterns in covid-19 pneumonia: implications for disease severity assessment - Khemchandani, Ajit Kumar; Shaikh, Hafeezullah; Khemchandani, Manisha (Journal of the Pakistan Medical Association, 2024)
Objective: To explore the incidence of liver function test derangement, the precise patterns of derangement, and their relationship with coronavirus disease-2019 pneumonia severity. Method: The retrospective study was conducted at the Dow University Hospital and the Ojha Institute of Chest Diseases, Karachi, and comprised consecutive data from December 16, 2020, to March 16, 2021, of adults of either gender who had nasal swabs positive for coronavirus disease-2019 on real-time reverse transcriptase-polymerase chain reaction. Data regarding patients' demographics, co-morbidities, addictions, laboratory results, and standard information was retrieved from electronic and manual records. The severity of the disease was determined based on World Health Organisation protocols. Data was analysed using SPSS 23. Results: Of the 344 patients, 235(68.3%) were males and 109(31.7%) were females. The overall mean age was 54.58±14.75 years, 187(54.4%) had severe coronavirus disease-2019 pneumonia and 157(45.6%) had non-severe disease at the time of admission. There was a significant prevalence of both mixed and cholestatic patterns of liver function test abnormality among the cases (p=0.046). The presence of a mixed pattern was linked to the disease severity (p<0.05). Advanced age and hypertension were significant risk factors for the development of severe coronavirus disease-2019 pneumonia (p<0.001 & p = 0.002). Conclusion: Liver function test abnormality and coronavirus disease-2019 pneumonia severity were fund to have a significant relationship. Key Words: SARS CoV-2, COVID-19-pneumonia, Liver function test, Pattern of LFT abnormality, Severe COVID pneumonia.